Impact of Financial Leverage on Market Value Added: Empirical Evidence from India - Pandya, Bhargav (Journal of Entrepreneurship, Business and Economics, 2016)
The paper aims at analyzing the impact of financial leverage on market value added in the context of companies listed on Bombay Stock Exchange and provide empirical evidence. The study covers 197 companies classified as A group companies listed on the Bombay Stock Exchange. The study period ranges from 2010 to 2014. Univariate linear regression and multiple regression analysis are used to test the relationship between measures of financial leverage and market value added. The results show that interest cover is the most significant predictor of market value added by companies listed on Bombay Stock Exchange. Univariately, debt equity ratio and debt ratios are found to be statistically significant in explaining variation in market value added of the sample companies. But when taken together, they are not significantly related to market value added of sample companies. The research was restricted to only those companies which are classified as A group companies on Bombay Stock Exchange. The study relied on Market Value Added as a measure of value creation. Other measures like, Economic Value Added, Created Shareholder Value, Total Shareholder Return could also be used to gauge the impact of financial leverage on the shareholder value creation. The study identifies interest cover as the most significant predictor of change in Market Value Added. Financial managers will thus be motivated to maintain higher interest cover to ensure higher value creation for their shareholders. Research paper Reference to this paper should be made as follows: Pandya. B. (2016). “Impact of Financial Leverage on Market Value Added: Empirical Evidence from India”, Journal of Entrepreneurship, Business and Economics, Vol. 4, No. 2, pp. 40–58.